Die Leistungsfähigkeit der Wissenschaft des Öffentlichen Rechts : Berichte und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Freiburg i. Br. vom 3. bis 6. Oktober 2007. - Hillgruber, Christian (De Gruyter, 2008)
The volume presents the reports and discussions held at the conference of the "Association of German Constitutional Law Teachers" in Freiburg from October 3rd to October 6th, 2007.
Keywords: International law -- Legal research -- Congresses.; Law -- Public Law -- Constitutional Law.; Law -- Public Law -- General Administrative Law.; Public law -- Study and teaching -- Germany -- Congresses.; Public law -- Germany -- Legal research -- Congresses.; International law -- Legal research.; Public law -- Study and teaching.; Germany.; Electronic books.; Conference papers and proceedings.